Plan de Negocios para la creación de un restaurante de comida fusión Japonesa en la ciudad de Santa Marta (2023)
This proposal focuses on the creation of a Japanese fusion restaurant in the city of Santa Marta. To demonstrate the level of approval of this project, a macroeconomic analysis, industry analysis, market research, organizational development of the industry and financial plan will be carried out. The research method will be descriptive, the primary research tools will be established by direct observation and the use of surveys, while the secondary information tools will be the official documents and reports used in the recognition and formulation process. In the economic and financial study, it was established that the initial investment of the present project is $64.563.057, and attractive indicators are obtained for its investment, with a NPV of 80.707.802, a PRI of 1,23 and finally an IRR of 42,47%, which shows that the investment project is feasible and profitable